The interactive effects of titanium dioxide nanoparticles and light on heterotrophic bacteria and microalgae associated with marine aggregates in nearshore waters. (October 2020) - Haynes, Vena N.; Ward, J. Evan
Abstract: Titanium dioxide nanoparticles (n-TiO2 ) are emerging contaminants and the ecological impact of these materials to the nearshore environment is largely unknown. The reactivity of n-TiO2 increases with light exposure, and the photocatalytic effects have been shown on cultures of bacteria and microalgae in the laboratory. The purpose of this study was to assess the response of natural bacterial and microalgal communities associated with marine aggregates to n-TiO2 under conditions similar to those found in the photic zone of nearshore waters. Nano and bulk TiO2 particles were incorporated into marine aggregates over 4 days under two light conditions: 6:18 and 0:24 (hours light:dark). The abundance and metabolic response of heterotrophic bacteria and viability of microalgae associated with aggregates were assessed. Although the proportion of living microalgae was unchanged, the abundance, total metabolic activity and functional diversity of heterotrophic bacteria were significantly altered by irradiated n-TiO2 . Graphical abstract: Image 1 Highlights: Marine aggregates and associated microorganisms were exposed to irradiated TiO2 nanoparticles. Irradiated TiO2 nanoparticles affected the bacterial abundance. Irradiated TiO2 nanoparticles affected the bacterial metabolic activity and diversity. Effects can be attributed to the "nano" size of the particles and photoreactivity.